MiR-369-5p inhibits the proliferation and migration of hepatocellular carcinoma cells by down-regulating HOXA13 expression. (February 2022) - Qian, Xinye; Wang, Yun; Hu, Wang; Xu, Xiaolei; Gao, Lu; Meng, Yongchang; Yan, Jun
Highlights: MiR-369-5p targeted HOXA13, and inhibited HOXA13 expression in HCC. MiR-369-5p mimic inhibited HCC cells viability, proliferation, migration, invasion and EMT processes. HOXA13 overexpression counteracted the effect of miR-369-5p mimic and promoted the biological behavior and EMT of HCC cells. Abstract: MicroRNA (miRNA) is vital to the progression of hepatocellular carcinoma (HCC). Thereinto, miR-369-5p could yield assorted effects on various cancers, but there are few reports concerning the effect of miR-369-5p on HCC. Thus this study aimed to investigate the effect and mechanism of miR-369-5p in HCC. The data of miR-369-5p and HOXA13 expressions in liver hepatocellular carcinoma (LIHC) were analyzed by starBase, and then the miR-369-5p expression in HCC tissues and cells was detected by quantitative real-time PCR. Subsequently, miR-369-5p mimic was transfected into HCC cells and then its effects on cell activities were evaluated by cell counting kit-8, colony formation, wound healing, transwell assays, respectively. Expressions of epithelial-mesenchymal transition (EMT)-related genes were determined by western blot. The targeting relationship between miR-369-5p and HOXA13 was predicted by Targetscan and verified by dual-luciferase reporter assay. Pearson correlation test was used to analyze the correlation between HOXA13 and miR-369-5p. The above assays were experimented again to investigate the effects of HOXA13 on biological activity and EMT of HCC cells. MiR-369-5p expression was down-regulated and HOXA13 expression was up-regulated in LIHC. MiR-369-5p targeted HOXA13 and the expression of miR-369-5p was negatively correlated with the HOXA13 expression. MiR-369-5p inhibited the viability, proliferation, migration and invasion of HCC cells, increased E-cadherin level and decreased N-cadherin and Vimentin expressions. Concurrently, HOXA13 overexpression could counteract the effects of miR-369-5p on biological activity and EMT-related biomarkers of HCC cells. To conclude, miR-369-5p inhibits the viability, proliferation, migration and invasion of HCC cells by repressing the expression of HOXA13.